The quick Python book - Ceder, Naomi R. (Manning, 2010)
"The Quick Python Book, Second Edition, is a clear, concise introduction to Python 3, aimed at programmers new to Python. This updated edition includes all the changes in Python 3, itself a significant shift from earlier versions of Python. The book begins with basic but useful programs that teach the core features of syntax, control flow, and data structures. It then moves to larger applications involving code management, object-oriented programming, web development, and converting code from earlier versions of Python. True to his audience of experienced developers, the author covers common programming language features concisely, while giving more detail to those features unique to Python"--Resource description page.